Widespread Use of Complementary and Alternative Medicine (CAM) among Non-Hodgkin Lymphoma (NHL) Survivors - Osian, S. Rausch (Leuk Lymphoma, 2014)
There are few studies examining complementary and alternative medicine (CAM) use and beliefs among non-Hodgkin lymphoma (NHL) survivors. 719 NHL patients from the University of Iowa/Mayo Clinic Molecular Epidemiology Resource who completed the 3-year post-diagnosis questionnaire were included in this study. 636 (89%) reported ever using CAM, with 78% utilizing vitamins, 54% alternative therapies and 45% herbals. Female gender was associated with increased overall CAM use (P<.0001) as well as use of vitamins (P<.0001), herbals (P=.006) and alternative therapy (P=.0002) for cancer. Older age (>60) was associated with increased vitamin use (P=.005) and decreased herbal use (P=.008). Among users, 143 (20%) believe CAM assists healing, 123 (17%) believe CAM relieves symptoms, 122 (17%) believe CAM gives a feeling of control, 110 (15%) believe CAM assists other treatments, 108 (15%) believe CAM boosts immunity, 26 (4%) believe CAM cures cancer, and 36 (5%) believe CAM prevents the spread of cancer.